(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The pervasive use of social media has transformed how adolescents perceive themselves, often shaping body image ideals and influencing self-esteem. Body Image Perception refers to how adolescents view and evaluate their physical appearance relative to societal and media standards. Self Esteem is an adolescent’s overall sense of self-worth and confidence, influenced by external validation and internal assessment. Peer Comparison refers to the process through which adolescents evaluate their appearance and achievements in relation to peers. Online validation is all about likes, comments, and feedback that reinforces self-perception positively or negatively. This study examined the association between social media usage, body image perception, and self-esteem among adolescents in selected secondary schools in Bamenda I Sub-division, North West Region of Cameroon. The study was guided by Social Comparison Theory (Festinger, 1954), which explains how adolescents evaluate themselves by comparing to peers and media figures; Objectification Theory (Fredrickson & Roberts, 1997), highlighting how societal focus on appearance fosters self-objectification; Self-Discrepancy Theory (Higgins, 1987), describing emotional discomfort from mismatches between actual and ideal selves; and Uses and Gratifications Theory (Katz, Blumler, & Gurevitch, 1974), which explains adolescents’ active engagement with media to fulfill needs such as social validation and entertainment. Employing a cross-sectional mixed-methods design, 250 adolescents were selected via stratified random sampling. Quantitative data were collected using standardized questionnaires on social media engagement, body image dissatisfaction, and self-esteem, while qualitative data were obtained via focus group discussions. Quantitative analysis included descriptive statistics, Pearson correlation, ANOVA, and multiple regression. Qualitative data were thematically analyzed. Results indicated a significant positive relationship between social media use and body dissatisfaction (r = .42, p < .001), and a significant negative relationship between body dissatisfaction and self-esteem (r = -.48, p < .001). Regression analysis revealed that social media exposure predicted 32% of the variance in self-esteem outcomes (R² = .32, F (3, 246) = 38.56, p < .001). Qualitative findings highlighted peer comparison, exposure to idealized images, and online validation as central factors influencing body image and self-perception. The study concludes that excessive social media engagement contributes to negative body image and lower self-esteem among adolescents. Strong recommendations include integrating digital literacy programs into the curriculum to teach adolescents critical thinking skills in interpreting social media content, especially regarding unrealistic beauty standards and edited images. Establish school-based counseling services were trained counselors can support adolescents struggling with body image or low self-esteem. Promote extracurricular activities such as sports, arts, and debate clubs that build confidence, resilience, and self-worth beyond physical appearance. Organize seminars and workshops on self-esteem, self-acceptance, and healthy social media use, involving teachers, parents, and students. Monitor and guide social media use at home by setting healthy screen-time limits and encouraging positive online engagement. Model positive body image and self-acceptance at home, avoiding negative body talk or comparisons that may reinforce insecurities. Encourage open communication with adolescents about the pressures they face online, creating a safe space for discussions without judgment. Promote alternative activities such as reading, sports, and volunteering that shift focus from appearance-based validation to skill-based or value-based achievement, awareness campaigns on responsible social media use, and parental guidance to mitigate adverse psychological outcomes.